The Transformation of Digital Money in the Framework of Islamic Law: The Potential Use of Bitcoin for Zakat - Lili Naili Hidayah; Ageng Triganda Sayuti; Muskibah Muskibah; Rema Syelvita; Pahlefi Pahlefi (Kosmik Hukum, 2026)
This study aims to analyze the legal position of Bitcoin as a potential object of zakat from the perspectives of Islamic law and Indonesian positive law, while examining the extent to which both legal systems provide legitimacy for the use of Bitcoin in zakat payment. This article discusses the transformation of digital money, specifically Bitcoin, within the framework of Islamic law by highlighting Bitcoin's growing relevance and controversy in Islamic finance. Using a juridical-normative approach, this study examines whether Bitcoin fulfills the legal requirements as zakatable property according to Islamic jurisprudence and analyzes its legal implications under Indonesian positive law. The findings indicate that although Bitcoin possesses economic value and may qualify as zakatable property, several legal and sharia issues remain, including value volatility, gharar (uncertainty), regulatory limitations, and the absence of comprehensive technical guidelines for zakat institutions. This article recommends developing an integrated legal framework through adaptive regulations, technical guidance for zakat institutions, and blockchain-based governance that complies with sharia principles to ensure legal certainty and transparency in digital asset-based zakat.